2000
DOI: 10.1038/76074
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in TGIF cause holoprosencephaly and link NODAL signalling to human neural axis determination

Abstract: Holoprosencephaly (HPE) is the most common structural defect of the developing forebrain in humans (1 in 250 conceptuses, 1 in 16,000 live-born infants). HPE is aetiologically heterogeneous, with both environmental and genetic causes. So far, three human HPE genes are known: SHH at chromosome region 7q36 (ref. 6); ZIC2 at 13q32 (ref. 7); and SIX3 at 2p21 (ref. 8). In animal models, genes in the Nodal signalling pathway, such as those mutated in the zebrafish mutants cyclops (refs 9,10), squint (ref. 11) and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
294
1
8

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 373 publications
(307 citation statements)
references
References 22 publications
4
294
1
8
Order By: Relevance
“…Our result is consistent with a recent report by Shen and Walsh (2005). This result is strikingly different from the human study, which revealed that loss of Tgif function is associated with human HPE, a typical ventral forebrain malformation (Gripp et al, 2000). This discrepancy suggests that additional genetic insults may also contribute to the HPE phenotype associated with patients bearing Tgif mutations, whereas the loss of TGIF function in mice may be compensated for by other TGF-␤ antagonists.…”
Section: Tgif ؊/؊ Embryos Show Normal Brain and Spinal Cord Patterningsupporting
confidence: 80%
See 3 more Smart Citations
“…Our result is consistent with a recent report by Shen and Walsh (2005). This result is strikingly different from the human study, which revealed that loss of Tgif function is associated with human HPE, a typical ventral forebrain malformation (Gripp et al, 2000). This discrepancy suggests that additional genetic insults may also contribute to the HPE phenotype associated with patients bearing Tgif mutations, whereas the loss of TGIF function in mice may be compensated for by other TGF-␤ antagonists.…”
Section: Tgif ؊/؊ Embryos Show Normal Brain and Spinal Cord Patterningsupporting
confidence: 80%
“…The human TGIF gene is mapped to 18p11.3, a critical region for HPE (Gripp et al, 2000). Mutations of TGIF have been found in various HPE patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HPE is etiologically heterogeneous, and a number of both environmental and genetic causes have been identified (Muenke and Beachy, 2000;Ming and Muenke, 2002). Mutations in seven genes have been noted to cause human HPE: SHH (Roessler et al, 1996(Roessler et al, , 1997, ZIC2 (Brown et al, 1998), SIX3 (Wallis et al, 1999), TGIF (Gripp et al, 2000), PTCH (Ming et al, 2002b), TDGF1 (De La Cruz et al, 2002), and GLI2 (Roessler et al, 2003). Several other candidate genes for HPE also exist (Kamnasaran et al, 2005).…”
Section: Introductionmentioning
confidence: 99%